Effects of school-based physical activity interventions on physical fitness and cardiometabolic health in children and adolescents with disabilities: a systematic review - Manojlovic, Marko; Roklicer, Roberto; Trivic, Tatjana; Milic, Rade; Maksimović, Nemanja; Tabakov, Roman; Sekulic, Damir; Bianco, Antonino; Drid, Patrik (Frontiers in Physiology, 2023)
Background: This study aimed to examine the influence of school-based physical exercise programs on physical fitness and cardiometabolic health in children and adolescents with disabilities. Methods: Web of Science, Scopus, and PubMed were thoroughly searched to identify relevant investigations. To be included in the systematic review, studies needed to fulfill the following inclusion criteria: (1) performed school-based physical exercise interventions; (2) parameters evaluated referred to health-related physical fitness (HRPF), skill-related physical fitness (SRPF), and cardiometabolic health; (3) a sample of participants consisted of children and adolescents with disabilities; (4) the mean age of respondents was less than 18 years; and (5) were written in the English language. Results: After searching the databases, a total of 18 studies met the eligibility criteria, and their outcomes were presented. Regarding types of physical exercise interventions, the most commonly implemented were combined aerobic and resistance training, aerobic exercise, sports games, adapted high-intensity interval training, as well as sprint interval training. The obtained results unambiguously demonstrated that applied exercise interventions improved HRPF components such as cardiorespiratory fitness, muscular fitness, and flexibility. In terms of the SRPF, agility, balance, coordination, and power were considerably enhanced following the school-based exercise. On the other hand, the influence on indices of body composition and cardiometabolic health is quite controversial. The majority of the available studies did not find favorable effects. Additionally, no adverse events were reported in 7 of 8 research, and adherence to exercise was approximately 92%. Conclusion: School-based physical exercise programs were very efficient in improving HRPF and SRPF in children and adolescents with disabilities, while the evidence concerning the variables of body composition and cardiometabolic health is inconclusive and warrants further investigations.